The concept of and the reasons for the formation of a religious crisis - Nowosielski, Mirosław (Studia Psychologica: Theoria et praxis, 2012)
Religious crises are a kind of psychological crises associated with the process of personality development. Authors dealing with religious crisis, in place of this term often applies the concept of conversion or doubt. The term is ambiguous and there is not finally define. Different authors to the religious crisis approach in two ways: Some are discussing this phenomenon more structurally, others describe them more in the context of development. The most comprehensive description of conversion we find on William James. As a scientist dealing with religion, James believed, that you can supernatural made make it more clear and you can try to interpret it psychologically. Given the different understanding of the religious crisis show multiple attempts to describe this phenomenon. All authors we see common elements like: a gradual or sudden, perceptible change in the religious life of the unit, annoying State of emotional tension and doubts in the field of religion. Crisis can end up positively, It means the unit enters the taller, darker level of faith, or can end up adversely, It means the person will go away from the faith completely or become agnostic.